Pengembangan Jaringan Irigasi dalam Upaya Intensifikasi Daerah Irigasi Pongok Bemban – Payak Ramai - Faskal, Faskal; Fitriani, Heni; Dewi, Ratna (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The Pongok Bemban-Payak Ramai Irrigation Area, with a potential area of approximately 13 ha, is a rice field area located in Pongok Village, Pongok Islands District, South Bangka Regency. The geographical location of Pongok Village, which is the outermost region of the Regency, makes the community highly vulnerable to difficulties in obtaining food due to uncertain weather and sea conditions. Currently, farmers can only plant rice once a year, during the rainy season. Additionally, several hectares of land are affected by sea tides that enter the rice fields. This issue is exacerbated by the simple irrigation network, lack of reservoirs, and proximity to the sea, which causes water to be wasted during the rainy season. Limited water sources and land are the main challenges for farmers and local governments, making the intensification of agricultural land and its irrigation network a top priority to increase the cropping index and land productivity. This study proposes an alternative solution, which is the construction of a weir equipped with a spillway and drain door to maximize existing water sources. The operation of weirs and sluice gates plays a crucial role in efforts to increase the cropping index and land productivity. The results of the intensification of the irrigation network establish a water balance with a planting pattern of 100% rice - 100% rice - 30% rice (IP 230), with the beginning of planting in November period I and a total harvest area of approximately 30 ha. A weir reservoir with a length of 500 m, width of 15 m, and depth of 2.5 m is designed to accommodate the third planting period (MT) in the dry season. Farmers' yields in three planting periods (IP 230) produce 150 tons of milled dry grain (MDG) or 90,000 kg of rice